Portal Berita Berbasis Web Pada PT. Jambi Ekspres Televisi (JEKTV) - Anwar , Syaiful; Sarjono, Sarjono (LPPM Universitas Dinamika Bangsa, 2022)
The development of technology has a positive impact in the delivery of news or information to the public to be easier and faster without any distance limitation in accessing the news. News portal is one of the media that is widely accessed by the public to get information through the internet. At PT. Jambi Ekspres Televisi (JEKTV) does not have a news portal to deliver such information quickly. The methodology used in designing this news portal is the prototype method. The purpose of designing this news portal is expected to help the company's performance in serving the news needed by the community quickly and the community can receive the news information up to date.